<span>By multiplying the first function with number 5, the graph will stretch by the order of five, meaning that in the second graph every value of the x will correspond to the 5 times bigger value of y than in the first case. Due to the +6 component, the second graph shifts to the left by 6 units.</span>
Answer: Hi!
Okay. So this equation we will solve using something called the distributive property. We use the distributive property to multiply the terms inside the parentheses (x and -2) by the term outside and in front of the parentheses (4). First, we would multiply 4 * x, which is 4x. Then, we would multiply 4 * -2, which is -8. Out equation now looks like this:
4x - 8 = 14
Our goal is to isolate the x, so now we'll use inverse operations to remove the -8 from the equation. The inverse operation for subtraction is addition, so we would add 8 to both sides:
4x - 8 = 14
+ 8 + 8
The eights cancel out, so we're left with this equation:
4x = 22
Last step! We're almost done. All we have to do now is divide 4 on both sides; in the term 4x, 4 is being multiplied by x, so the inverse operation would be division.
4x ÷ 4 = x
22 ÷ 4 = 5.5
Our equation now looks like this:
x = 5.5
So, 5.5 is equal to x! This would be your answer!
Hope this helps!
Answer:
D) 5
Step-by-step explanation:
Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Divide 2 from all terms within the equation:
(2y)/2 = (10x - 8)/2
y = (10x)/2 - (8)/2
y = 5x - 4
Note the slope-intercept form:
y = mx + b
y = y
x = x
m = slope
b = y-intercept.
In this case, 5 is in place of m, or your slope.
D) 5 is your answer.
~
When solving for a variable, you get the variable you're trying to solve for on one side and everything to the opposite of that variable.
We have the equation <span>5w + 9z = 2z + 3w.
Usually the variable we're solving for we want on the left. But it's fine to have it on the right side, too.
Let's subtract 9z from the left-hand side. That way, the 5w will be alone on the left-hand side.
And remember, anything we do on one side we do to the other side.
</span><span>5w + 9z - 9z = 2z + 3w - 9z
</span><span>5w = -7z + 3w
The 3w term on the right-hand side needs to be removed. So, subtract each side by 3w.
5w - 3w = -7z + 3w - 3w
2w = -7z
Now, we need to divide each side by 2 to see what the w variable is equal to.
2w / 2 = -7z / 2
w = -7z / 2 or w = -3.5z
So, w is equal to -3.5z.
</span>
4x-6= x+6
4x= x + 12
5x= 12
X= 12/5
X= 2.5